Human-related barriers to low employee involvement in continuous improvement initiatives: A phenomenological study of manufacturing workers in Indonesia - Aris Eko Wibowo; Thomas Sukardi; Widarto Widarto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
Continuous Improvement (CI) has become a fundamental management philosophy for achieving sustainable competitiveness in the manufacturing industry. However, despite its widespread adoption, many CI initiatives fail due to human‐related barriers that hinder implementation at the organizational level. This study aims to identify and analyze the key human factors that impede CI implementation in Indonesian manufacturing industries while exploring strategies to overcome these challenges. Using an exploratory qualitative design, data were collected through in-depth interviews with 15 manufacturing practitioners and analyzed using thematic analysis. The findings reveal seven major human-related inhibitors to successful CI implementation: complacency, misperception, irritability, individualism, work rigidity, frustration, and stress. Collectively, these factors erode motivation, weaken collaboration, and intensify resistance to organizational change, thereby limiting organizational learning and performance improvement. The results corroborate existing literature emphasizing the significance of human and cultural aspects in sustaining CI initiatives. To address these barriers, the study highlights the importance of fostering a supportive organizational culture that promotes psychological safety, teamwork, and continuous incremental learning through the Kaizen philosophy. Management interventions should focus on strengthening human engagement, realistic goal setting, and reward mechanisms that value collective effort and continuous learning. This study contributes to the growing body of knowledge on CI by providing an in-depth understanding of the human dimensions of continuous improvement within manufacturing contexts in developing countries. The findings provide both theoretical insights and practical guidance for leaders seeking to cultivate sustainable CI cultures driven by people rather than processes.